Perceptions of Community Interest Toward the Traditional Food “Kue Cucur Bandan” in Air Teras Village, Seluma Timur Sub-District - Alzen Alzen; Hesti Nur’aini; Lina Widawati (Journal of Multidisciplinary Research, 2026)
Cucur bandan cake is a traditional food of the people of Seluma Regency, Bengkulu Province, made from rice flour and brown sugar (palm sugar), which is a typical food of the people of the area. A study has been conducted that aims to study the processing of cucur bandan cake, analyze the perception of interest of the people of Air Teras Village, East Seluma District towards cucur bandan cake, and analyze their business. Qualitative descriptive research was conducted on 100 respondents who assessed cucur bandan samples sold by 20 sellers in Air Teras Village. The results of the study revealed that cucur bandan cake is processed using a simple method that has been passed down from generation to generation. Public perception of cucur bandan cake is good, with an average value of 29.35